Comparative analysis of switching frequency in DTC-CBSVM and FOC of three-level NPC PMSM drive for EV applications - Rakesh Shriwastava; Balajee Maram; Yogesh S. Pawar; Jyoti P. Rothe; Dinesh S. Wankhede; Hema Kale (Institute of Advanced Engineering and Science, 2026)
This paper presents a comparative analysis of switching frequency performance in direct torque control with carrier-based space vector modulation (DTC-CBSVM) and field-oriented control (FOC) of permanent magnet synchronous motor (PMSM) drives fed by a three-level neutral point clamped (NPC) inverter. PMSM drives are widely utilized in electric vehicles (EVs) due to their high efficiency, torque density, and reliability. However, the selection of an appropriate control strategy significantly influences inverter switching frequency, system efficiency, and overall drive performance. The DTC-CBSVM approach provides fast torque response and reduced torque ripple, whereas the FOC technique ensures precise control of flux and torque with smoother operation. In this study, both methods are implemented and evaluated under identical operating conditions. Simulation results highlight the trade-offs between dynamic response, switching frequency, and harmonic performance. The findings serve as a reference for selecting optimal control strategies for efficient PMSM-based NPC inverter drives in EV applications.